Where is the Foundation of African Gender? The Case of Malawi (Nordic Journal of African Studies, 2002)
The conceptual framework of feminism, as a reactionary ideology, basically consists of 'power', 'woman', 'rights', and 'equality'. The same can be said of African feminism, which has on its priority list such goals as self-determination, which have economic overtones sewn on a materialistic metaphysic. African womanism, despite its pretensions to seeking co-operation or its advocacy for interdependency between men and women, uses a model of conscientisation of women that is foreign to Africa, and runs the risks of obscurantism, vulgarism, inauthenticity, and irrelevance. To put it cryptically, African womanism 'can't want and can't not want' men at the same time. Although gender has made tremendous strides in conscientising women about their plight vis-à-vis male-dominance, its future in Africa demands that it re-position itself appropriately. At least it must re-think three theories, that is, the labour theory, economic theory, and social theory. (Ed.)